2022
DOI: 10.1038/s42004-022-00625-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid de novo discovery of peptidomimetic affinity reagents for human angiotensin converting enzyme 2

Abstract: Rapid discovery and development of serum-stable, selective, and high affinity peptide-based binders to protein targets are challenging. Angiotensin converting enzyme 2 (ACE2) has recently been identified as a cardiovascular disease biomarker and the primary receptor utilized by the severe acute respiratory syndrome coronavirus 2. In this study, we report the discovery of high affinity peptidomimetic binders to ACE2 via affinity selection-mass spectrometry (AS-MS). Multiple high affinity ACE2-binding peptides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…Importantly, this study identified peptide-based binders with avidity enhanced inhibition capacity towards the ex vivo derived native protein. We anticipate that high-throughput FPS measurements in tandem with automated approaches for ligand synthesis will aid in similar projects advancing the rational optimization of effectors with unnatural building blocks 38 and other multimeric effectors, including multivalent protein-carbohydrate interactions 39 . The resulting high avidity binders will expand the toolbox of versatile chemical biology probes to advance our understanding of protein function and localization e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this study identified peptide-based binders with avidity enhanced inhibition capacity towards the ex vivo derived native protein. We anticipate that high-throughput FPS measurements in tandem with automated approaches for ligand synthesis will aid in similar projects advancing the rational optimization of effectors with unnatural building blocks 38 and other multimeric effectors, including multivalent protein-carbohydrate interactions 39 . The resulting high avidity binders will expand the toolbox of versatile chemical biology probes to advance our understanding of protein function and localization e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this study identi ed novel binders with avidity enhanced inhibition capacity towards the ex vivo derived native protein. We anticipate that HT FPS measurements in tandem with automated approaches for ligand synthesis will aid in similar projects advancing the rational optimization of effectors with unnatural building blocks (Zhang et al, 2022) and other multimeric effectors, including multivalent protein-carbohydrate interactions (Tsouka et al, 2021). Such high avidity binders could contribute to advance our understanding of protein function and localization by expanding the toolbox of versatile chemical biology probes.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, a platform for accelerating drug discovery should combine high chemical diversity with the rapid identification of lead compounds selected from libraries. Recent strategies combining display techniques based on affinity selections and mass spectrometry techniques have enabled direct structural analysis of selected candidates [22,133,134]. The great advantage of this system is that no additional reaction for phenotype-genotype linkage is required, as the information of selected compounds can be directly deduced from the phenotypic sequence.…”
Section: Mass Spectrometry Elucidates Peptidomimetics With High Affin...mentioning
confidence: 99%
“…We first highlight the advantages of CFPS systems as a promising platform for the peptidomimetics production, and then discuss key display technologies crucial to linking the expressed products to their genotype, which allows the selection of peptidomimetics with the biological functions of interest from a library. We also describe recent technologies developed to characterize peptidomimetic molecule libraries using mass spectrometry [22]. Next, we present recent efforts made to incorporate non-canonical monomers into a peptide polymer backbone followed by the formation of non-peptide backbone i.e., esters [23,24], thioamides [25], and thioesters [26] rather than polypeptides using a CFPS platform.…”
Section: Introductionmentioning
confidence: 99%